(3NRGfI GdCOH hdH dHGH dSGf GdYQHs - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s; (3eMeO Hf GdMSf GdQVj GdCSJQGHGPj , fLe GdOjf,J (B686 (3g` s ((3Ydj Hf eMeO Hf eUWai GdTgjQ HGHf QLH hHGHf GdJQLeGf, GdLRGFQj GdeOfj s)
(3ChdgG (B:s
(3CeG HYO, ajbhd GdHZOGOj, gPG TQM ThGgO TQM GdcGajI hgh cJGH Yca Ydjg fMGQjQ GdYdeGA s
(3BNQgG (B:s
(3hGHf CMeQ TGYQ ESdGej JbOeJ JQLeJg aj GdTGgO GdSJjf HYO GdCQHY eFg Je GdLRA GdChd ef NRGfI GdCOH s
(3TQM ajg ThGgO TQM GdQVi GdGSJQGHGPj GdcGajI GHf GdMGLH s
(3hHgG fXGe GdJYbjHI YfO fgGjI cd cQGSIs
(3HChdgG agQS ddThGgOs
(3HChdgG Jedc hhba cJHg GdTfbjWj HNWg aj GdeOjfI GdefhQI YGe (B1288(3g``s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdfMhs